PENCIPTAAN BUKU ESAI FOTOGRAFI KESENIAN WAYANG THENGUL SEBAGAI UPAYA MELESTARIKAN BUDAYA TRADISIONAL BOJONEGORO - Fernandez, Riyansa England; Bahruddin, Muh; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Seeing the development of more advanced age and a lot of culture entering society lulled will make things that can be categorized as modern culture. More community members who choose to follow the culture from the outside compared to the local culture, one of the local culture that began enthusiasts it is a Wayang. Wayang is already widely known throughout the international community, but not all cultures for traditional Wayangs have the same fate. The original Wayang local culture many areas even endangered. Local tradional culture also includes cultural diversity must be preserved. The lack of a vigorous publications mainly through books can threaten the preservation of local culture that has not been disclosed. One was found in the district. Bojonegoro in East Java is an area that borders the province of Central Java, in which there is a large royal heritage acculturation that are different. Wayang Thengul is one of the local culture that has not been revealed endangered. In this study show and introduces how artists struggle and consistency Wayang Thengul predominantly elderly in struggling in todays modern era to the public outside of Bojonegoro through media photographic essay book.Â Keywords: local culture, Bojonegoro, Wayang Thengul, Preserving, Essays Book Photography